1999
DOI: 10.1089/jop.1999.15.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crocin Analogs on Ocular Blood Flow and Retinal Function

Abstract: Ischemic retinopathy and age-related macular degeneration are the leading ocular diseases that cause blindness. The etiology of these diseases is due in part to the reduction of blood flow in the retina and/or choroid. Crocin analogs isolated from Crocus sativus L. were found to significantly increase the blood flow in the retina and choroid and to facilitate retinal function recovery. Increased blood flow due to vasodilation presumably improves oxygenation and nutrient supply of retinal structures. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 12 publications
0
30
0
2
Order By: Relevance
“…There are numerous synthetic (10-15) as well as natural compounds (16)(17)(18)(19), which were reported to facilitate ocular blood flow and retinal function recovery after ischemic insult. It is hoped …”
Section: Discussionmentioning
confidence: 99%
“…There are numerous synthetic (10-15) as well as natural compounds (16)(17)(18)(19), which were reported to facilitate ocular blood flow and retinal function recovery after ischemic insult. It is hoped …”
Section: Discussionmentioning
confidence: 99%
“…They significantly increased blood flow in the retina and choroid and facilitated retinal function recovery. However, it seems that disaccharide analogues of crocin were less potent than monosaccharide ones (Xuan et al , ). Recent experiments showed that higher concentrations of vitreous glutamate damage the retina, as induced by chronic ocular hypertension in rabbits.…”
Section: Comparative Evaluation Of Saffron In the Canon And In Modernmentioning
confidence: 99%
“…It has been reported that saffron derived compounds like crocetin showed significant effects on coronary heart disease by inhibiting lipoprotein oxidation [33, 39], on neurodegenerative diseases [33, 39-44], on retinal function recovery by increasing retinal blood flow [33, 45], on reducing blood pressure and maintaining kidney function [46] and also used as anticonvulsive agent [33, 47]. Most notable discovery in relation to crocetin is to enhance oxygen diffusivity during shock and reperfusion that ultimately lead to increased ATP production [48, 49].…”
Section: Pharmacological Properties Of Crocetinmentioning
confidence: 99%